2017
DOI: 10.1016/j.evolhumbehav.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country relationships between life expectancy, intertemporal choice and age at first birth

Abstract: Humans, like other animals, typically discount the value of delayed rewards relative to those available in the present. From an evolutionary perspective, prioritising immediate rewards is a predictable response to high local mortality rates, as is an acceleration of reproductive scheduling. In a sample of 46 countries, we explored the cross-country relationships between average life expectancy, intertemporal choice, and women's age at first birth. We find that, across countries, lower life expectancy is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 47 publications
2
39
1
Order By: Relevance
“…Indeed, as has been found in studies of theory of mind development (e.g., Shahaeian, Peterson, Slaughter, & Wellman, 2011;Wellman, Fang, Liu, Zhu, & Liu, 2006), there may still be robust cultural variations in the steps that children acquire diverse instantiations of the capacity. To this end, future research may wish to investigate the crosscultural development of other future-oriented behaviors, such as tool acquisition and subsequent use (see Suddendorf, Nielsen, & Von Gehlen, 2011), acting for future desire states (see Atance & Meltzoff, 2006), intertemporal choice (see Bulley & Pepper, 2017;Metcalf & Atance, 2011;Mischel, Shoda, & Rodriguez, 1989), deliberate practice (see Brinums, Imuta, & Suddendorf, 2017), external reminder setting (see Redshaw, Vandersee, Bulley, & Gilbert, 2018), and affective forecasting (see Gautam, Bulley, von Hippel, & Suddendorf, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as has been found in studies of theory of mind development (e.g., Shahaeian, Peterson, Slaughter, & Wellman, 2011;Wellman, Fang, Liu, Zhu, & Liu, 2006), there may still be robust cultural variations in the steps that children acquire diverse instantiations of the capacity. To this end, future research may wish to investigate the crosscultural development of other future-oriented behaviors, such as tool acquisition and subsequent use (see Suddendorf, Nielsen, & Von Gehlen, 2011), acting for future desire states (see Atance & Meltzoff, 2006), intertemporal choice (see Bulley & Pepper, 2017;Metcalf & Atance, 2011;Mischel, Shoda, & Rodriguez, 1989), deliberate practice (see Brinums, Imuta, & Suddendorf, 2017), external reminder setting (see Redshaw, Vandersee, Bulley, & Gilbert, 2018), and affective forecasting (see Gautam, Bulley, von Hippel, & Suddendorf, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that women's age at first birth is younger when extrinsic mortality risks are higher (Low et al, 2008). One possible explanation for this acceleration of reproductive scheduling is that it offsets the fitness cost of high extrinsic mortality by increasing the chance of reproducing before death (Bulley & Pepper, 2017…”
Section: Study 2: Childhood Harshness and Collective Action In The Eumentioning
confidence: 99%
“…Specifically, harsher ecologies tend to be associated with psychological traits such as an immediate reward orientation and a shorter time horizon (Bulley & Pepper, 2017;Griskevicius et al, 2011). One possible reason for this is that people living in harsher and unpredictable environments are less likely to reap the benefits of deferred rewards.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using survey data from more than 40 countries finds that the proportion of "impatient citizens" (i.e. those who chose the sooner-smaller reward in a single hypothetical survey question) in a country is negatively related to the country's average life expectancy, and that adding life expectancy to the equation eliminates the negative country-level relationship between impatience and age at first birth (Bulley & Pepper, 2017). The latter results, although not directly addressing causality due to the cross-sectional nature of the data, may suggest that it is environmental mortality cues (as proxied by life expectancy) that influence both short-run orientation and early-reproduction decisions.…”
Section: Discussionmentioning
confidence: 99%